Perbedaan Orientasi Kerja Antara Generasi Y dan Generasi Z di Perusahaan Startup: Temuan dari Indonesia - Syarfina Mahya Nadila; Nadia Yovani; Andhika Ajie Baskoro (Universitas Pendidikan Ganesha, 2024)
This study aims to analyze the differences in the work orientation of Generation Y and Generation Z workers in startup companies based on generational differences, gender, religion, property ownership, domicile, and office location. This research uses a quantitative approach with a survey method. The results of this study show that both Generation Y and Generation Z workers who work in Startups have the same work orientation regarding gender, religion, place of residence, ownership status, and office location. This research is expected to extend knowledge about the characteristics of Generation Y and Generation Z workers. In addition, this research is expected to become evidence-based to tailor specific regulations related to work orientation among Generation Y and Generation Z.